E-Portfolios for self-regulated and co-regulated learning: A review - Lam, Ricky (Frontiers in Psychology, 2022)
The reflective component of e-Portfolios is said to help students improve second or foreign language writing in terms of motivation and academic results. Despite this positive advocacy, scholars remain unclear about how e-Portfolios can develop students’ self-regulatory abilities in writing classrooms, especially when students engage in complex e-Portfolio construction processes with peers, parents, teachers, their community, digital tools, and online resources. Recently, researchers have argued that not only do e-Portfolios promote self-regulated learning, but they also support co-regulation of learning wherein the latter is socially mediated by curriculum design, instructional materials, and in-class interaction patterns. Indeed, students’ inner development of self-regulatory capacity is closely influenced by external forces, which deserve more scholarly investigation. The review fills this gap by emphasizing that besides self-regulated learning, e-Portfolios can support students’ co-regulation of learning by way of their connectivity, visibility, and circulation. This review has four sections. The first section defines key concepts, namely e-Portfolios, self-regulated, co-regulated, and socially shared-regulated learning, and introduces how e-Portfolios foster self-regulation of learning in second language writing. The second section unpacks two conceptual models that underpin self-regulated and co-regulated learning relating to e-Portfolios. The third section presents a brief review, showcasing how e-Portfolios featuring self-regulation of learning can also support co-regulation of learning. The final section recommends strategies that facilitate self-regulation and co-regulation of learning in e-Portfolios reciprocally, and discusses implications for pedagogy and research.